Handbook of vacuum arc science and technology : fundamentals and applications - Sanders, David M.; Boxman, R. L.; Martin, Philip J. (Materials science and process technology series. Electronic materials and process technology., 1995)
Describes the basic physics and technological applications of vacuum arcs. Part I describes basic physics of the vacuum arc, beginning with a brief tutorial review of plasma and electrical discharge physics, then describes the arc ignition process, cathode and anode spots which serve as the locus for plasma generation, and resultant interelectrode plasma. Part II describes the applications of the vacuum arc for depositing thin films and coatings, refining metals, switching high power, and as sources of intense electron, ion, plasma, and x-ray beams.